Politeness Strategy Analysis of Speech Acts between Lecturer and Students in English Classroom - Muhammad Sahrain; Ria Hendriani; Herman Herman (Civiliza Publishing, Indonesia., 2026)
This research examines linguistic politeness strategies within the context of English language instruction at Universitas Qamarul Huda Badaruddin Bagu. Politeness serves as a central focus within pragmatics, a specialized branch of linguistics. Specifically, this study concentrates on the interactions between students and lecturers during the instructional process. Employing a qualitative ethnographic approach, the study involved one lecturer and 30 students from the Cooperative Economics Department. Data were collected through non-participant classroom observations and semi-structured in-depth interviews. The findings showed that the application of Leech’s six maxims within the classroom serves as a vital instrument for academic diplomacy. These include the Tact Maxim, Generosity Maxim, Approbation Maxim, Modesty Maxim, Agreement Maxim, and Sympathy Maxim. Each maxim functions complimentary to balance the rights and obligations of both lecturers and students. The implementation of these maxims successfully minimizes the perceived power distance between the lecturer and students, thereby fostering an equitable classroom atmosphere. Ultimately, this practice cultivates an academic culture rooted in mutual respect, productivity, and empathy.